2017
DOI: 10.1186/s12887-017-0841-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with anemia among Sri Lankan primary school children in rural North Central Province

Abstract: BackgroundDespite interventions, childhood anemia is still a major public health problem in low and middle income countries. Purpose of the present study is to determine factors associated with anemia among rural primary school children in Sri Lanka, a country undergoing rapid socioeconomic changes.MethodsMulti stage cluster sampling was used to select 100 rural schools in NCP and a maximum of 50 children aged 60–131 months were enrolled from each school. Self-administered questionnaires were sent to parents. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 27 publications
1
14
1
Order By: Relevance
“…In the current study, our initial analysis found a negative association between anaemia (i.e., anaemia and normocytic anaemia) and overweight/obesity in contrast to previous studies, some of which failed to report any association between anaemia and overweight/obesity [43,44,45], whereas others detected a positive association between Hb concentration and BMI [43,44]. To further examine the correlation between Hb concentration and BMI among children in the current study, we performed an additional analysis and also found a significant positive relationship between Hb and BMI-for-age z-score.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…In the current study, our initial analysis found a negative association between anaemia (i.e., anaemia and normocytic anaemia) and overweight/obesity in contrast to previous studies, some of which failed to report any association between anaemia and overweight/obesity [43,44,45], whereas others detected a positive association between Hb concentration and BMI [43,44]. To further examine the correlation between Hb concentration and BMI among children in the current study, we performed an additional analysis and also found a significant positive relationship between Hb and BMI-for-age z-score.…”
Section: Discussioncontrasting
confidence: 95%
“…In contrast, we found no association between anaemia and any of the selected socio-economic factors investigated such as maternal employment, maternal education, or household income, findings in accordance with Alelign et al’s study in Ethiopian children [49]. In our additional analyses, we also found no association between Hb and selected socio-economic factors, in contrast to Amarasinghe et al who reported a significant positive relationship between parental education and Hb concentrations of Sri Lankan children [44]. Similarly, although not statistically significant, children of mothers with better education also had higher Hb concentrations in our study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Overall prevalence of anaemia in this study was 27.9% and Thenmaradchi zone had a significantly higher prevalence than other zones. A similar study in the North Central Province among 4460 primary school children showed an overall prevalence of anaemia of 17.3% 13 . This shows that there is a difference in the prevalence of anaemia between northern and north central province indicating that the demographic factor has a role in the prevalence.…”
Section: Discussionmentioning
confidence: 70%
“…(Table 4) Mild anaemia was seen in 22.7% and moderate anaemia in 4.1% of the study population. The cross sectional study done in North Central Province found mild and moderate anaemia in 9.4% and 7.6% of children respectively 13 . Prevalence of anaemia among school children aged 5-19 years in Ethiopia in 2017 was 23% and among them 61%, 21% and 11% had mild, moderate, and severe anaemia respectively 16 .…”
Section: Discussionmentioning
confidence: 95%